(untitled) (International Journal of Physiotherapy, 2017)
The researchers and authors are publishing their work in the scientific journals for accomplishment and acknowledgement for what they have achieved in their field of study. As an effect of digitalization now a day many journals are readily available in the World Wide Web for good. At the same time, anecdote of misconduct, negligence and deception of the publishers are also getting higher and higher in this regard. Thus, choosing a trustworthy journal is important for every researcher especially young researchers to avoid potential damage to any one of the purposes of publishing an article.Since many factors are influencing to choose a right and trustworthy journal for manuscript submission and at the same time is more critical for any of the young researchers and authors as well. Hence, this short communication as preamble;emphasizing on the factors such as the visibility of a journal, manuscript processing procedures, the governance and the impact factor will possibly be a prelude for the young researchers and authors those who are all trying to submit a manuscript and get it published their research work in trustworthy journals to achieve any of purposes of publishing.